VD_FINDINFO Arrêt / 2024 / 707 vom 25. Oktober 2024 - VD Tribunal cantonal (2024)
SURASSURANCE, RENTE D'INVALIDITÉ, RENTE COMPLÉMENTAIREAA, INDEMNITÉ JOURNALIÈRE | 15 LAA, 16 LAA, 19 LAA, 20 LAA, 6 LAA, 69 LPGA